A comprehensive approach to environmental and human factors into product/service design and development. A review from an ergoecological perspective. (November 2016) - Saravia-Pinilla, Martha H.; Daza-Beltrán, Carolina; García-Acosta, Gabriel
Abstract: This article presents the results of a documentary-exploratory review of design methods and concepts associated with human and environmental factors, based on a qualitative-quantitative analysis of coincidences with the fundamentals of ergoecology and in line with sustainable dynamics, with a view to putting the principles of ergoecology into practice in product/service design and development. 61.6% of 696 documents found represent work on conceptual developments, while the remaining 38.4% refer to design methods. Searches were refined using Nvivo-10 software, and 101 documents were obtained about theoretical aspects while 17 focused on the application of methods, and these formed the analysis universe. The results show how little concern there is for working comprehensively on human and environmental aspects, and a trend toward segmentation of human and environmental aspects in the field of product/service design and development can be seen, at both concept and application/methodology levels. It was concluded from the above that comprehensive, simultaneous work is needed on human and environmental aspects, clarity and conceptual unity, in order to achieve sustainability in practical matters and ensure that ergoecology-compatible design methods are applied. Highlights: The need of approaching and intervening simultaneously human and environmental problems has been identify. This are the results of a systematic review of design concepts and methods associated with human and environmental factors. It shows conceptual and methodological segregation between human factors and environmental factors in published documents. Hints are giving towards a comprehensive approach based on ergoecology to strengthening decision making processes. The paper contributes to recognize methods for product/service design and development with perspective human-environmental.